Trends and Peculiarities of Educational Migration in Modern Russia - S. I. Chernykh; A. A. Izgarskaya (Дискурс)
Introduction. The modern educational space are transformed under the influence of many factors in the conditions of approaching V techno-economic paradigm. The determining factors are technological breakthroughs that qualitatively change not only educational practices, but also the nature of the educational space. The globalization of the educational services market, the growing economic inequality and the inequality of opportunities in different regions force large numbers of people to migrate in search of optimal educational conditions. In turn, the educational migration is increasingly turning into an economic mechanism for generating profit and it is becoming a kind of indicator of the regional educational systems’ competitiveness. The study of these processes is relevant today. The authors analyze the current trends and peculiarities of education migration in Russia.Methodology and sources. The methodological basis of the work is the interdisciplinary approach. The range of attitudes has already been set forth within the framework of sociocultural and activity approaches (N. Yu. Harari, J. Knight), the economic layer of considering problems related to theory migration processes (E. G. Ravenstein, E. Lee, M. Piore, I. Wallerstein and others), studies of Russian economists, political scientists and sociologists (A. N. Dzhurinsky, I. V. Ivakhnyuk, etc.).Results and discussion. The history of the national academic capital formation shows that today internationalization is a leading trend in its development along with the economic, technological and intellectual components. This means that educational migration as part of the internationalization process is becoming an indicator of the regional educational systems’ competitiveness. The general trend can be traced quite clearly: the higher quality of the educational services is provided and the ecosystem of the educational space is more comfortable, then the vector of migration is more relevant to this region. This tendency has just begun to be studied in Russia. But it is quite obvious today that the regional Russian educational space is clearly ‘‘skewed’‘, and the state educational policy carried out is not always contributing to its leveling.Conclusion. There is a necessity for the realization of the positive potential of educational migration and the overcoming of its negative consequences: multivariate analysis of the processes of educational migration, not only at the level of individual universities and regions, but on all-Russian scale; the formation of such an education ecosystem in the regions, which would reduce the gap between the ‘‘Centre and the regions’‘ and as well as between ‘‘universities leaders’‘ and ‘‘universities of more lightweight category’‘.